Meningkatkan Gerak Lokomotor Melompat Melalui Permainan Halang Rintang - Mansur, Muhammad Fadhil Naim; Sudirjo, Encep; Rahman, Aam Ali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research was to determine the effect of obstacle course games on locomotor jumping movements. This research uses quantitative methods using an experimental approach. The one-group pre-test post-test design was the design used in the research. This research was conducted at one of the elementary schools in Selomerto District, Wonosobo Regency. The sample in this study consisted of 28 fifth grade students aged 11-12 years. The average score on the pretest was 4.36, while the average score on the posttest was 5.96. The standard deviation for the pretest is 1.471 and for the posttest is 1.644. Through the paired sample test, there are results from the hypothesis test with a calculated value of -9.279 which is higher than the table value of 1.703 from the T table (with 27 degrees of freedom), and the significance level is 0.000, which is less than 0.05. The results of this research show that the null hypothesis (H0) is rejected, while the alternative hypothesis (Ha) is accepted. The results of this research show that the obstacle course game has a significant impact on locomotor jumping movements. The obstacle course game makes students more enthusiastic in moving, especially in jumping through obstacles. Keywords: jump, locomotor movement, obstacle course game